Psychological Drivers and Daily Spending Habits: How the Latte Factor Shapes Financial and Compulsive Behavior Among Millennials - Mukhibatul Hikmah (Penerbit Jurnal Indonesia, 2025)
This study aims to examine the influence of self-esteem and self-control on personal financial behavior and compulsive buying among millennials. Guided by Social Cognitive Learning Theory, the research explores how psychological factors shape financial habits, including the tendency toward the latte factor—small, repeated expenses that accumulate over time and impact long-term financial stability. A quantitative explanatory approach was used, involving a survey of 150 millennial respondents selected through accidental sampling. Data were analyzed using path analysis with WarpPLS. Findings reveal that self-esteem significantly affects both self-control and personal financial behavior. Although self-esteem does not have a direct significant effect on compulsive buying, its indirect influence through self-control and financial behavior is statistically significant (β = -0.063; p < 0.001). This indicates that individuals with higher self-esteem tend to exhibit stronger self-control and healthier financial behavior, which in turn reduces the likelihood of engaging in compulsive or impulsive purchases, including recurring minor spending (latte spending). Furthermore, self-control positively impacts personal financial behavior and negatively affects compulsive buying. Good financial behavior also significantly lowers the tendency for compulsive spending. These results highlight the importance of strengthening self-regulation and psychological awareness to prevent harmful spending habits—particularly in the digital era, where micro-spending often goes unnoticed but can significantly affect millennials’ financial well-being